A biochemical mini-research project: Can yeast fermentation decrease the amount of phytic acid in soybeans? - Lai, Quyen D.; Apuzzo, C. Fiore; Jones, Marjorie A. (Edelweiss Applied Science and Technology, 2024)
This mini-research project studied the effect of yeast fermentation on the nutritional value of soybeans, specifically the concentration of phytic acid, protein, and lipids. With prior experience in protein and lipids analysis, the students (n = 12) in this laboratory applied their critical thinking and problem-solving skills to design and conduct their own assays for phytic acid extraction and quantification. All students decided to use ion exchange chromatography to extract phytic acid and UV/vis spectroscopy with Wade’s reagent for phytic acid quantification. These methods were evaluated by the students as simple and effective in analyzing phytic acid from soybeans. This project allowed students to use several of the methods used in other parts of the semester in addition to adding new methods to evaluate a research question.